Reglas básicas de la práctica policial y funcionamiento interno de la Policía - Yñiguez Navas, Agustín (Cuadernos de Trabajo Social, 2007)
This article analyzes the basic rules that direct Police practice and examines some of the main elements of the professional culture of the Police force. Special attention is paid to its sense of the group, the level of discretion utilized in its actions and the use of force. The relationship between legitimacy and authority in Police actions is also investigated. These elements are key in the decision-making process of members of the Police force when they interact with civilians. Their characteristics make up the foundation of Police practice. Its acknowledgement makes it possible to organize the ways in which Police intervention works and makes it easier to comprehend the internal mechanisms that govern Police actions. This, therefore, is the main contribution of the article to our understanding of the present state of affairs.